Formulation and stabilization of oil-in-water nanoemulsions using a saponins-rich extract from argan oil press-cake. (25th April 2018) - Taarji, Noamane; Rabelo da Silva, Cezar A.; Khalid, Nauman; Gadhi, Chemseddoha; Hafidi, Abdellatif; Kobayashi, Isao; Neves, Marcos A.; Isoda, Hiroko; Nakajima, Mitsutoshi
Highlights: Surface-active extracts were prepared from argan oil press-cake. Formulation of O/W nanoemulsions using 50% (v/v) ethanolic extract as emulsifier. Good physical stability of emulsions prepared at 100 MPa up to 4 passes. The nanoemulsions were sensitive to NaCl addition and to acidic pH. Abstract: In this study, we formulated and stabilized oil-in-water nanoemulsions using a crude extract from argan press-cake as sole emulsifier. Various extracts from argan press-cake were prepared in order to select the most surface-active one(s) foreseeing emulsions preparation. Fifty percent (v/v) ethanolic extract reduced the interfacial tension to a minimum value at both MCT oil and soybean oil interfaces (12.7 and 10.5 mN m −1 respectively). This extract was also effective at producing fine emulsions with small droplet sizes ( d 3, 2  < 115 nm) and good physical stability using different oils such as soybean oil, MCT oil and fish oil and at conventional homogenization conditions (100 MPa for 4 passes). On the other hand, the emulsions were very sensitive to NaCl addition (≥25 mM) and to acidic pH (<3) indicating that the main stabilization mechanism is electrostatic, likely due to the presence of surface-active compounds with ionizable groups such as saponins.